2021
DOI: 10.3390/en14144379
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Approaches for Assessing a High Temperature Borehole Thermal Energy Storage Facility at Linköping, Sweden

Abstract: Assessing the optimal placement and design of a large-scale high temperature energy storage system in crystalline bedrock is a challenging task. This study applies and evaluates various methods and strategies for pre-site investigation for a potential high temperature borehole thermal energy storage (HT-BTES) system at Linköping in Sweden. The storage is required to shift approximately 70 GWh of excess heat generated from a waste incineration plant during the summer to the winter season. Ideally, the site for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Advances in downhole logging techniques and lab-based experiments have contributed to a more nuanced understanding of these petrophysical attributes. Such insights have been pivotal in optimizing drilling practices [19][20][21][22], which have evolved from traditional vertical wells to more complex deviated and horizontal trajectories [23,24]. High-resolution reservoir simulations and geomechanical models are frequently employed to predict the impacts of different drilling and completion scenarios [25].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in downhole logging techniques and lab-based experiments have contributed to a more nuanced understanding of these petrophysical attributes. Such insights have been pivotal in optimizing drilling practices [19][20][21][22], which have evolved from traditional vertical wells to more complex deviated and horizontal trajectories [23,24]. High-resolution reservoir simulations and geomechanical models are frequently employed to predict the impacts of different drilling and completion scenarios [25].…”
Section: Introductionmentioning
confidence: 99%
“…Mogensen [22] reported values λ g = 2.69 W/m K and R b = 0.1266 K/W m, while Reuss [19] reported that λ g = 2.2 W/m K and ρc = 2.8 MJ/m 3 K. Gehlin [20] indicated that the thermal conductivity of the ground when a borehole is filled with grout is 3.45 W/m K, while it is 3.62 W/m K when filled with water. In recent years, studies in [23][24][25][26][27][28][29][30][31] showed improvements and applications of the TRT procedure for evaluating BHE efficiency. Luo et al [23] studied the influence of an unstable power input on the unacceptable errors of the TRT measured data.…”
Section: Introductionmentioning
confidence: 99%